First gase-phase metallicity gradients of 0.1 ≲ z ≲ 0.8 galaxies with MUSE. Issue 4 (18th May 2018) - Carton, David; Brinchmann, Jarle; Contini, Thierry; Epinat, Benoît; Finley, Hayley; Richard, Johan; Patrício, Vera; Schaye, Joop; Nanayakkara, Themiya; Weilbacher, Peter M; Wisotzki, Lutz
ABSTRACT: Galaxies at low-redshift typically possess negative gas-phase metallicity gradients (centres more metal-rich than their outskirts), whereas it is not uncommon to observe positive metallicity gradients in higher-redshift galaxies (z ≳ 0.6). Bridging these epochs, we present gas-phase metallicity gradients of 84 star-forming galaxies between 0.08 < z < 0.84. Using the galaxies with reliably determined metallicity gradients, we measure the median metallicity gradient to be negative (-0.039^+0.007_-0.009 dex kpc^-1 ). Underlying this, however, is significant scatter: (8 ± 3) per cent [7] of galaxies have significantly positive metallicity gradients, (38 ± 5) per cent [32] have significantly negative gradients, (31 ± 5) per cent [26] have gradients consistent with being flat. (The remaining (23 ± 5) per cent [19] have unreliable gradient estimates.) We notice a slight trend for a more negative metallicity gradient with both increasing stellar mass and increasing star formation rate (SFR). However, given the potential redshift and size selection effects, we do not consider these trends to be significant. Indeed, once we normalize the SFR relative to that of the main sequence, we do not observe any trend between the metallicity gradient and the normalized SFR. This is contrary to recent studies of galaxies at similar and higher redshifts. We do, however, identify a novel trend between the metallicity gradient of a galaxy and its size. Small galaxies ( r d < 3 kpc) present a large spread in observed metallicity gradients (both negative and positive gradients). In contrast, we find no large galaxies ( r d > 3 kpc) with positive metallicity gradients, and overall there is less scatter in the metallicity gradient amongst the large galaxies. These large (well-evolved) galaxies may be analogues of present-day galaxies, which also show a common negative metallicity gradient.